Twenty-five years of Genomes OnLine Database (GOLD): data updates and new features in v.9. Issue Volume 51:Issue D1(2023) (1st November 2022) - Mukherjee, Supratim; Stamatis, Dimitri; Li, Cindy Tianqing; Ovchinnikova, Galina; Bertsch, Jon; Sundaramurthi, Jagadish Chandrabose; Kandimalla, Mahathi; Nicolopoulos, Paul A; Favognano, Alessandro; Chen, I-Min A; Kyrpides, Nikos C; Reddy, T B K
Abstract: The Genomes OnLine Database (GOLD) (https://gold.jgi.doe.gov/ ) at the Department of Energy Joint Genome Institute (DOE-JGI) continues to maintain its role as one of the flagship genomic metadata repositories of the world. The ever-increasing number of projects and metadata are freely available to the user community world-wide. GOLD's metadata is consumed by scientists and remains an important source for large-scale comparative genomics analysis initiatives. Encouraged by this active user engagement and growth, GOLD has continued to add new components and capabilities. The new features such as a public Application Programming Interface (API) and Ecosystem landing page as well as the growth of different entities in this current GOLD v.9 edition are described in detail in this manuscript.